The Odessa period of academic of AUAS A.O. Sapegin life: the prerevolutionary years (1903-1917) - M. V. Apostol (History of science and technology, 2014)
The article investigates the prerevolutionary years of the Odessaperiod life ofacademicof AUAS A.O. Sapegin. It is provedthat it is theseyearswerea period of formationfor Sapeginas a scientist andorganizer.